Performance of Angora goats, mohair production, and farmer income in extensive livestock systems of north Patagonia, Argentina - Sacchero, Diego; Gonzalez, Ezequiel B.; Maurino, Julia; Lopez, Miriam; Cortes, Maria Victoria; Alvarez, Rocío; Bidinost, Franca (Frontiers in Animal Science, 2023)
In Argentina the mohair production is limited exclusively to the Patagonia region. This activity takes place under different biophysical conditions and with marked seasonality in the climatic conditions and productivity of natural grasslands. The present study aimed to analyze Angora goat performance, mohair production and income in two contrasting environments of northern Patagonia, the East and the West regions. To this end, body weight (BW), body condition score (BCS), fleece weight (FW) and mohair samples were collected between the spring of 2019 and the autumn of 2022. Fiber quality analyses included fiber diameter (MFD), percentage of medullated fibers (MED and kemp fibers (KMP). Finally, the income per shearing (IPS) was estimated based on the individual data and prices obtained in public tenders. Analysis of variance (ANOVA) was performed and the effects considered (all fixed) were region, shearing season (autumn and spring), age and their interactions. The results for the BW, BCS, FW and MFD showed lower values during spring in the farms of the West, reflecting the adverse environmental conditions of this region. In general, the BW of goats in the East was 15 % to 25 % higher compared to the goats in the West (P < 0.01). While fleece weight difference between regions reached 25 % to 32 % in mature old goats (P < 0.01). The autumn MFD was similar between regions (P > 0.05) and higher compared to spring MFD (P < 0.05). The KMP content in the West was two-fold higher than that in the East region where was recorded 1.21 % (P <0.01). Regarding the effect of the season, KMP and MED content was higher in autumn than in spring (P < 0.01). The IPS values were lower in spring. The highest IPS (US 15.1) was obtained at the age of two permanent incisors. Results showed that 70 of the 100 best-ranked goats by IPS were from the East. This information is useful to understand and describes the productive performance of Angora goats and mohair quality at the farm level in extensive systems of Argentine Patagonia.